Visibility, Territory, and Community: The National Museum of Anthropology in Madrid’s Heritage Landscape (Cadernos de Sociomuseologia, 2026)
This study examines the conceptual and functional transformation of the National Museum of Anthropology (NMA) within the framework of contemporary approaches to critical, social, and territorial museology, with the aim of establishing the need for and relevance of its comprehensive museographic renovation. Based on a historical-theoretical analysis that reviews the transition from the traditional museum toward participatory and community-oriented models, it is possible to contextualize the specific challenges facing the NMA in relation to its surroundings, precisely because it is an institution located in a strategic setting in the city of Madrid, which has been a World Heritage Site since 2021. Thus, the museum has limited public visibility and a weak institutional identity within the capital’s cultural ecosystem. This tension constitutes a critical point for its strategic repositioning within its urban context.Between 2023 and 2024, the institution conducted an audience study that serves as the empirical basis for this document. Its findings reveal a significant gap between the museum’s symbolic and territorial potential and its social recognition, as well as the need to update its narratives, strengthen its institutional communication, and improve its integration into the urban environment. The analysis reveals that the audience demands more contemporary, intercultural, and critical discourses, as well as greater openness on the part of the museum toward participatory and co-responsible practices. These demands align with international trends that place participation, epistemic diversity, and heritage justice at the center of museum practice. This project demonstrates that the renovation of the permanent exhibition is not merely a museographic intervention, but also a strategic opportunity to reposition the MNA as a relevant cultural agent, aligned with the principles of accessibility, diversity, social sustainability, and citizen participation promoted by current public and cultural policies.Keywords: Museology; World Heritage; audience studies; territory; social participation.